(untitled) (Scientific journal of the Fergana State University, 2025)
The article theoretically analyzes the transmission of natural solar radiation through atmospheric layers, taking into account Rayleigh scattering in air molecules. The spectral and angular distributions of solar radiation fluxes, including diffusely reflected, transmitted, and unscattered radiation emerging from the atmospheric layers, were calculated. The calculation of diffuse radiation intensity was carried out within the framework of the theory. Chandrasekhar’s S,T-matrix theory was developed using the factorization method.